Respuesta :

A general exponential expression is something like:

A^n

This means that we need to multiply the number A by itself n times.

Using that we will get (-2)^6 = 64

With that definition, we can rewrite:

(-2)^6 = (-2)*(-2)*(-2)*(-2)*(-2)*(-2)

So we just need to solve the above expression.

Also, remember the rule of signs:

(-)*(-) = (+)

We will get:

(-2)*(-2)*(-2)*(-2)*(-2)*(-2) =  [(-2)*(-2)]*[(-2)*(-2)]*[(-2)*(-2)]

                                        =  4*4*4 = 16*4 = 64

Then we got:

(-2)^6 = 64

If you want to learn more, you can read:

https://brainly.com/question/17172630